2011
DOI: 10.1007/s11274-011-0879-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of chlorpyrifos by bacterial consortium isolated from agriculture soil

Abstract: Organophosphorous pesticides are widely used in agriculture to control major insect pests. Chlorpyrifos is one of the major organophosphorous pesticides which is used to control insects including termites, beetles. The widespread use of these pesticides is hazardous to the environment and also toxic to mammals, thus it is essential to remove the same from the environment. From the chlorpyrifos contaminated soil nine morphologically different bacterial strains, one actinomycete and two fungal strains were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(52 citation statements)
references
References 20 publications
(20 reference statements)
0
49
0
3
Order By: Relevance
“…(Lakshmi et al 2009). A consortium consisting of Klebsiella sp., Pseudomonas aeruginosa, Pseudomonas stutzeri, and Pseudomonas putida isolated from chlorpyrifos contaminated agricultural soil, which could degrade chlorpyrifos even at 500 mg L -1 , highlights the potential use of consortia to clean up contaminated sites (Sasikala et al 2012). Degradation efficiency and optimal conditions for efficient chlorpyrifos degradation by co-culture of chlorpyrifos degrading bacterium Serratia sp.…”
Section: Biodegradationmentioning
confidence: 99%
“…(Lakshmi et al 2009). A consortium consisting of Klebsiella sp., Pseudomonas aeruginosa, Pseudomonas stutzeri, and Pseudomonas putida isolated from chlorpyrifos contaminated agricultural soil, which could degrade chlorpyrifos even at 500 mg L -1 , highlights the potential use of consortia to clean up contaminated sites (Sasikala et al 2012). Degradation efficiency and optimal conditions for efficient chlorpyrifos degradation by co-culture of chlorpyrifos degrading bacterium Serratia sp.…”
Section: Biodegradationmentioning
confidence: 99%
“…There were 5 dominant bands (a, n, o, u, x) sequenced. Three out of the five bands were similar to chlorpyrifos-degrading bacteria in CWs (Pinjari et al, 2012;Sasikala et al, 2012;Feng et al, 2014). Hence, there might be considerable potential degrading ability of chlorpyrifos in each treatment.…”
Section: Discussionmentioning
confidence: 83%
“…The efficiency of different microbial degradation pathways has also been studied. Numerous studies have concentrated on the selection of specific pesticide-degrading bacteria in different pesticide-polluted samples (Lakshmi et al, 2009;Sasikala et al, 2012). Nevertheless, research on the effect of pesticides on microbial community dynamics should not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…When growing in minimal salt medium containing 2 mg.ml Chlorpyrifos as the solitary carbon source it was demonstrated that as high as 90% chlorpyrifos was utilized by MAS-1 just in 24 h (Munazza et al, 2012). In a parallel study, Sasikala et al (2012) isolated nine different bacteria from chlorpyrifos contaminated soil of which four were further used in preparation of consortium for the degradation of pesticide. In another study, it has been reported that 4 strains of Pseudomonas isolated from a water waste irrigated agri-soil in India, were able to utilize chlorpyrifos as an exclusive carbon source (Bhagobaty and Malik 2008).…”
Section: Bioremediation Of Organophosphorousmentioning
confidence: 99%